Coupling the beams: How controlled extraction methods and FTIR-spectroscopy, OM and SEM reveal the grinding of starchy plants in the Pontic steppe 36, 000 years ago. (February 2022) - Longo, L.; Birarda, G.; Cagnato, C.; Badetti, E.; Covalenco, S.; Pantyukhina, I.; Skakun, N.; Vaccari, L.; Terekhina, V.; Sorrentino, G.
Highlights: " legacy " objects cured in museums can be investigated by means of STEM disciplines. Microscopy coupled with FTIR IR-SR provide proxies to characterize ancient starch. FTIR spectroscopy and synchrotron light validate ancient starch candidates. Careful sampling strategies are crucial to extract "reliable" ancient starch grains. Abstract: A selection of five ground stones from Pontic Steppe sites dating back to the Early Upper Palaeolithic (EUP) was used as test-cases to be analysed by combining wear-traces and use-related biogenic residues (U-RBR). The artifacts studied can be termed " legacy " objects, excavated even many decades ago and kept in museum storage facilities. This type of storage might be considered putatively prone to contamination. The multidimensional contextual approach we designed integrates the structural analysis of biogenic residues by means of visual light optical and electronic beams microscopy (OM/VLM and SEM) coupled with FTIR microspectroscopy and imaging (using both conventional and synchrotron infrared sources). SEM and FTIR are meant to provide high resolution morphological and chemical profiles and their coupled analysis revealed the presence of starch grains from the used areas of the stone tools. The goal of this paper is to present a reasoned streamlined procedure to collect appropriate samples suitable to detect the presence of ancient starches from ground stones tools recovered in museum collections.